Construction of zinc selenide microspheres decorated with octadecylamine-functionalized reduced graphene oxide as an effective catalyst for the dual-mode detection of chloroquine phosphate. (June 2022) - Ganguly, A.; Hwa, K.-Y.
Abstract: Zinc selenide microspheres were constructed using a simple hydrothermal technique at 180°C. It was ultrasonically treated with reduced graphene oxide modified with octadecylamine alkyl amine to form a hybrid nanocomposite. The optical, structural, and functional analysis by ultraviolet (UV) absorbance, X-ray diffraction, Fourier transform infrared spectroscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy revealed the crystal nature of the microspheres and the successful formation of the nanocomposite. Field emission scanning electron microscopy and transmission electron microscopy were done to study the morphological properties of the material. It was further used to fabricate a dual-modality sensor using both electrochemical and absorbance techniques for the detection of antimalarial drug chloroquine phosphate (CQP), which was used for the treatment of COVID-19 (SARS-CoV-2) virus. For electrochemical detection, the sensor showed a very low detection limit of 1.43 nM at a linear working range of 0.199–250.06 μM and a high sensitivity of 43.912 μA/μM/cm 2 . For UV-based detection, the sensor showed a very low detection limit of 6.88 nM at a linear working range of 0.045–7.324 μM. The sensor showed excellent analyte recovery rate for real-time analysis in biological as well as environmental samples. The results suggested that the sensor is effective for the detection of CQP with feasibility for future commercialization. Graphical abstract: Image 1 Highlights: Highly efficient zinc selenide microspheres were synthesized and successfully conjugated on octadecylamine-modified reduced graphene oxide to form a hybrid composite. The composite shows good catalytic activity as well as optical activity by effective covalent synergism. The oxidation of CQP drug in NaOH electrolytic medium is reported for the first time. Sensitive detection of CQP was possible with lower limit of detection at 1.43 nM (electrochemically) and 6.88 nM (ultraviolet based). The real-time applicability was successfully implied in biological and environmental samples.